PENGARUH KEPUTUSAN INVESTASI, KEPUTUSAN PENDANAAN DAN KEBIJAKAN DEVIDEN TERHADAP NILAI PERUSAHAAN - Nur Indah Fitriyasari; Ardi Paminto; Muhammad Amin Kadafi (Jurnal Ilmu Manajemen Mulawarman (JIMM), 2018)
This research aims to know the Affect of Investment Decision, Funding Decision and Dividend Policy on Firm Value. This research uses secondary data which from  Indonesian Capital Market Directory (ICMD). The populations are the whole go public companies which listed in Indonesia Stock Exchange (IDX). Sampling was done by purposive sampling. The analysis technique used is Multiple Linier Regression.The results show that investment decision has positive and significant effect to firm value. Funding decision and dividend policy have negative effect to firm value.   Keywords :    investment decision, funding decision, dividend policy , firm value.